The Citation Factor Reconsidered: New Alternative for Tourism and Hospitality Research - Korstanje, Maximiliano E (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2018)
This note of research deals with the obsession of tourism scholars for citation impacts. Here I analyze not only the problems of tourism research but also how commercial publishers monopolized the production and the academic market through the imposition of the sense of prestige. We hold the thesis that the citation impact corresponds with a narcissist trend oriented to undermine the critical thinking. AUTOR Maximiliano E Korstanje - Doutorando. Professor na Universidad de Palermo, Buenos Aires, Argentina. Currículo: http://palermo.academia.edu/MaximilianoEKorstanje/CurriculumVitae. E-mail: maxikorstanje@hotmail.com REFERENCES Aramberri, J. (2001). The host should get lost: Paradigms in the tourism theory. Annals of Tourism Research, 28(3), 738-761. Link Bramwell, B., & Lane, B. (2011). Critical research on the governance of tourism and sustainability. Journal of Sustainable Tourism, 19(4-5), 411-421. Link Cohen, E. (1988). Authenticity and commoditization in tourism. Annals of Tourism Research, 15(3), 371-386. Link De Kadt, E. (1979). Social planning for tourism in the developing countries. Annals of Tourism Research, 6(1), 36-48. Link Jafari, J. (2001). The scientification of tourism. In: Smith, V. L. & Brent, M. (edts) Hosts and guests revisited: Tourism issues of the 21st century, 28-41. USA: Cognizant Communication Corporation. Krippendorf, J. (2010). Holiday makers. London: Taylor & Francis. Korstanje, M. E. (2017). Failed Prestige: problems and quandaries of tourism discipline over 40 years. In: R. Krebs (ed). Tourism and Hospitality: perspectives, opportunities, and challenges. New York: Nova Science Publishers. Li, X., & Petrick, J. F. (2008). Tourism marketing in an era of paradigm shift. Journal of Travel Research, 46(3), 235-244. Link MacCannell, D. (1976). The tourist: A new theory of the leisure class. Berkeley: University of California Press. McKercher, B., & Tung, V. (2015). Publishing in tourism and hospitality journals: Is the past a prelude to the future? Tourism Management, 50, 306-315. Link Riesman, D., Glazer, N., & Denney, R. (2001). The lonely crowd. New Haven: Yale University Press. The bookseller (2012). Academics call for boycott Elsevier. Link Tribe, J. (1997). The indiscipline of tourism. Annals of Tourism Research, 24(3), 638-657. Link Tribe, J. (2010). Tribes, territories and networks in the tourism academy. Annals of Tourism Research, 37(1), 7-33. Link Urry, J. (1990). The consumption' of tourism. Sociology, 24(1), 23-35. Link Weber, M. (2009). From Max Weber: essays in sociology. Abingdon: Routledge.